Risk factors for postpartum psychiatric disorders: A systematic review - Andini Dyah Sitawati; Hilmia Fahma; Muhammad Fadhlan La Tabari; Tri Ratnaningsih; Putri Mayang Sari Antariksa; Agustiawan Agustiawan (Science Midwifery, 2025)
Introduction: Postpartum psychiatric disorders, particularly postpartum depression, are one of the most common psychological complications affecting maternal and neonatal well-being. These conditions are often underdiagnosed and undertreated, particularly in developing countries. Identifying risk factors is crucial for prevention and early detection. Objective: This systematic review aims to identify and analyze risk factors contributing to postpartum psychiatric disorders based on scientific evidence from 2015 to 2025. Methods: A literature search was conducted through PubMed, Scopus, ScienceDirect, and Web of Science databases using the keywords ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œpostpartum depression,ÃƒÂ¢Ã¢â€šÂ¬Ã‚Â ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œpsychiatric disorder,ÃƒÂ¢Ã¢â€šÂ¬Ã‚Â and ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œrisk factors.ÃƒÂ¢Ã¢â€šÂ¬Ã‚Â Included articles were observational human studies, written in English or Indonesian, reporting risk factors and postpartum psychiatric outcomes. Of the 1,026 articles screened, nine studies met the inclusion criteria. Results: The most consistent risk factors found included a history of previous psychiatric disorders, low social support, perinatal stress, low economic status, obstetric complications, and postpartum immunological dysregulation. Eight of the nine studies showed a significant association (p < 0.05). Conclusion: Postpartum psychiatric disorders are multifactorial, influenced by biological, psychological, and social factors. Preventive efforts should focus on antenatal screening, strengthening social support, and monitoring the mother's mental state after delivery.